Challenges In The Global Project Management Organization : Developing Contemporary Solutions - Ylönen, Antti (My University, 2020)
The main goal of project management is to ensure successful project delivery fulfilling the time, quality, monetary and functionality requirements. The project management methodology is considered to consist of ten knowledge areas that are together forming the theory of project management. When developing the project management, it is important to remember the differences of each project when using theory as a foundation for development. This research targets company’s project management processes, tools and reporting possibilities towards the customer in the global environment. The aims of this thesis is to determine the challenges that globalization generates in project management. The research question is set to determine the current maturity level of project management and identify possibilities to increase the maturity by developing tools and processes. The biggest challenge for the study is the global aspect of the target company’s project management, where project team members are located all over the World. Naturally, this aspect generates challenges in communication and finding in an aligned way of working. The research is heavily based on the project management methodology and qualitative interviews. The literature helped build a theoretical framework and data collected from interviews, helped in identifying challenges and problems especially when comparing data against the theory. The interviewees were from six different countries around the world and based on the interviews and theory, biggest challenges were lack of a common way of working principles between product lines, differences between project management departments within the target company, the usage of highly customized, standalone software and lack of integration towards ERP system. In conclusion, the main solution for these challenges is a common project management tool, connected to the ERP system. Thereby the way of working would automatically align within one tool and all project-related data would be stored in one place. These changes would solve most communicational problems and decrease the time spent on communication. Gained benefits could be taken into use in terms of unifying and automating internal and external reporting. When the information is up to date and stored in a commonplace, sharing the data is easy and safe. This thesis includes also suggestions for customer reporting and an example of a Power Bi report template for a customer. The goal is to create an automated report where a customer would always have access. Consequently, the workload generated by reporting can be decreased and increase customer satisfaction.

Projektihallinnan tavoite on varmistaa projektien toimitus sovitusti ja sujuvasti, täyttäen aikataululliset, laadulliset, rahalliset ja toiminnalliset vaatimukset. Projektinhallinta katsotaan koostuvan kymmenestä eri osa-alueesta, mitkä muodostavat projektinhallinnan teorian. Projektihallintaa kehittäessä, onkin tärkeää muistaa projektien ainutlaatuisuus, kun teoriaa käytetään pohjana kehityksessä. Tämä tutkimus tutkii kohdeyrityksen projektinhallinta prosesseja, työkaluja ja raportointimahdollisuuksia asiakkaalle globaalissa ympäristössä. Diplomityön tavoitteena on määritellä globalisaatiosta johtuvat projektihallinnan haasteet. Työn tutkimuskysymyksenä on määritellä nykyinen projektihallinnan kypsyys ja tunnistaa mahdollisuuksia parantaa kypsyyttä kehittämällä prosesseja ja työkaluja. Työn Suurimpana haasteena on kohdeyrityksen projektihallinnan globaali ominaisuus, minkä takia projektitiimin jäsenet tulevat ympäri maailmaa. Tämä luonnollisesti luo haasteitta kommunikoinnissa ja yhteisten työskentelytapojen saavuttamisessa. Tutkimus perustuu vahvasti projektihallinnan teoriaan sekä laadullisiin haastatteluihin. Teoriaa apuna käyttäen, teoreettinen viitekehys saatiin luotua ja haastatteluista saadut tulokset hyödynnettiin ongelmien tunnistamisessa. Haastateltavia oli kuudesta eri valtiosta ympäri maailmaa. Haastatteluiden sekä teorian perusteella, suurimpia tunnistettuja kehityskohteita olivat yhteisien työskentelytapojen puuttuminen tuotelinjojen välillä, useiden rinnakkaisten sekä sisäkkäisten projektihallintaorganisaatioiden eriävät toimintatavat sekä toimintamallit ja itsenäisien organisaatioiden omien työkalujen puutteellinen integroiminen yrityksen ERP systeemiin. Loppujen lopuksi, keskeiseksi ratkaisuksi tunnistettiin yksi, yhteinen projektihallintatyökalu, kytkettynä yrityksen ERP systeemiin. Tällöin työskentelytapojen olisi pakko muuttua samankaltaisiksi, milloin myös kaikki projektikohtainen tieto olisi yhdessä paikassa, Tällöin kommunikaatioon liittyvät kuormittavat tekijät saataisiin myös osittain eliminoitua. Saatuja hyötyjä voidaan myös hyödyntää sekä sisäisen että ulkoisen raportoinnin yhtenäistyksessä ja automatisoinnissa, kun tieto on ajan tasalla sekä varastoituna paikkaan, mistä sen jakaminen eri alustojen kautta on helppoa ja turvallista. Diplomityö sisältää myös ehdotuksia asiakasraportointiin ja esimerkin mahdollisesta raportointipohjasta hyödyntäen Power bi raportointiohjelmistoa. Tavoitteena on luoda automaattisesti päivittyvä ajan tasalla oleva raportti mihin asiakkaalla olisi aina pääsy. Näin raportoinnista syntyvää kuormitusta voidaan tehokkaasti vähentää, parantaa asiakastyytyväisyyttä ja lähentää yhteistyötä.
Keywords: project management; projects; project managers; globalisation; global problems; reporting; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics